Ocorrência de infecções fúngicas em pacientes internados com Covid-19 em dois centros do Nordeste do Brasil - Balde, Mohamed Saido (2023)
COVID-19 is an infectious disease that was declared a pandemic on March 11, 2020 by the World Health Organization (WHO). The aim of this study was to assess the frequency of invasive fungal infections (IFIs) in patients diagnosed with COVID-19 in two public hospitals in Fortaleza, Ceará, Brazil. A cross-sectional study was carried out by reviewing the medical records of patients with COVID-19 who were diagnosed with IFIs during hospitalization at the Hospital São José de Doenças Infecciosas and the Hospital Universitário Walter Cantídio. Patients of both sexes and any age with a confirmed diagnosis of COVID-19 and IFI were included. The diagnosis of COVID-19 was confirmed by reverse transcription polymerase chain reaction (RT-PCR) of nasal/oropharyngeal swabs or other respiratory samples. The IFI diagnosis was based on the isolation of the fungus in blood samples, buffy coat, cerebrospinal fluid, bone marrow aspirates and respiratory samples. The period from March 1, 2020 to March 31, 2022 was considered. Epidemiological, clinical and laboratory data were obtained by reviewing medical records and laboratory records. Statistical analysis was conducted using Data Analysis and Statistical Software (STATA 13.0). Forty cases of IFIs were identified, twenty-six of which were healthcare-related infections (HAIs) and 14 endemic mycoses. Of the HAIs, twenty were cases of candidemia, four of COVID-19 associated pulmonary aspergillosis (CAPA), two cases of ventilator-associated fungal pneumonia (VAP) caused by Fusarium solani and Saprochaete capitata. Of the endemic mycoses, 12 cases were of disseminated histoplasmosis (DH), one case of coccidioidomycosis and one of neurocryptococcosis. HAIs occurred mainly in male patients, over 60 years of age, with comorbidities and severe cases of covid-19, who required intensive care. Endemic mycoses occurred in young adults with previous HIV infection. Overall mortality was 52.5% (21/40); among patients with HAIs, death occurred in 61.5% (16/21), 60% (12/20) among cases of candidemia, 50% (2/4) among cases of CAPA and in both cases of VAP. Regarding endemic mycoses, death occurred in 23.8% (5/21); 41.6% (5/12) among HD cases. In the bivariate analysis, severe COVID-19, dyspnea and hemodialysis were associated with death in patients with HAI. In the multivariate analysis, there was no independent risk factor for death in patients with HAIs. In conclusion, IFIs have contributed to an increase in morbidity and mortality in patients with COVID-19, highlighting the need to identify fungi in these patients for appropriate antifungal treatment.